DDX59-AS1 is a prognostic biomarker and correlated with immune infiltrates in OSCC - Sun, Yang; Zhou, Qianrong; Sun, Jian; Bi, Wei; Li, Ruixue; Wu, Xingwen; Li, Ni; Song, Liang; Yang, Fei; Yu, Youcheng (Frontiers in Genetics, 2022)
Background: lncRNAs play a critical role in multiple steps of gene regulation associated with tumor progression. However, the role of DDX59-AS1, a lncRNA, remains equivocal, particularly in oral squamous cell carcinoma (OSCC). In this study, the expression of DDX59-AS1 and its association with immune infiltration were investigated, and its prognostic value in OSSC was evaluated. Methods: OSCC patients were collected from The Cancer Genome Atlas (TCGA) database. The expression of DDX59-AS1 in OSCC and healthy tissue was compared using Wilcoxon Rank Sum Test. The relationship between DDX59-AS1 and clinicopathological features was analyzed using Logistic regression. Gene ontology (GO) terminology analysis, gene set enrichment analysis (GSEA) and single sample GSEA (ssGSEA) were utilized to interpret the enrichment pathway and functionality, and to quantify the immune cell infiltration of DDX59-AS1. The correlation between survival and DDA59-AS1 was evaluated by Kaplan-Meier analysis and Cox regression. The prognostic impact of DDX59-AS1 was predicted by the nomogram based on Cox multivariate analysis. Results: High expression of DDX59-AS1 was significantly correlated with T stage, clinical stage, race and age (P<0.05). Multivariate survival analysis demonstrated that the high expression of DDX59-AS1 was associated with lower overall and specific survival rates. The prognosis prediction was validated by the nomogram and calibration curves. The expression of DDX59-AS1 was negatively correlated with Mast cells, Tfh, T cells, Treg and B cells, and positively related with the Tgd infiltration level. Conclusions: DDX59-AS1 played a crucial role in the progression and prognosis of OSCC, and was potentially a predictive biomarker for OSCC.